Control and management of water quality for Nile tilapia fish in net tanks based on fuzzy modeling - Mastelini, Vinícius; Ramos Queiroz, Timóteo; Almeida Gabriel Filho, Luís Roberto; Mollo Neto, Mario (Revista Brasileira de Engenharia de Biossistemas, 2023)
Being classified as one of the most important species for fish farming, the Nile tilapia has seen a huge increase in breeding worldwide. As in any cultural medium, dealing with the quality of the medium in which it is grown guarantees a large part of the success of the process, being of equal importance, in this case, the quality of the water. Taking advantage of existing mathematical models, humans were able to measure and design best practices in virtually all areas, pointing to its great functionality, this article used the Fuzzy logic mathematical model together with Mamdani inference to analyze water quality scenarios and their consequences, various environments, variables, capable of directly affecting fish farming. The purpose was to use the MatLab scientific software to cross these variables with the possible output scenarios, facilitating the producer’s decision-making. As a result of the research, it was possible to develop an algorithm to be embedded in a mobile application in the future with fuzzy mathematical modeling, with a Mamdani inference system for management and control of water quality in Nile Tilapia fish farming. The same will be made available to these breeders, since it has a structure of rules, aiming at the delivery of scientific information that collaborates with the best cultivation practices, improving production and profitability, through decision support to fish farmers.